Stopband enhanced patch‐type filter using common‐mode feeding method based on multilayer liquid crystal polymer lamination technology. Issue 4 (16th December 2022) - Huang, Feng; Aliqab, Khaled; Alsharari, Meshari; Lu, Jiayuan
Abstract: In this study, a new common‐mode feeding approach to the 2‐D square patch resonator is proposed and applied in the design of bandpass filter (BPF) with wideband harmonic suppression. Different from the conventional single‐point feeding structure, the proposed one has two physical feeding points on the patch. It is indicated from the electric field distributions that the presented feeding method can not only support the excitation of the desired fundamental TM01 mode, but also enable the rejection of high‐order modes by selecting proper feeding positions. For demonstration, a second‐order BPF centred at 4.0 GHz with wide stopband suppression has been implemented by using multilayer liquid crystal polymer circuit technology. Moreover, benefitting from mixed‐coupling, a transmission zero is introduced to improve the filtering selectivity. Measured and simulated results are in good agreement with each other, validating the proposed feeding concept. Abstract : A new common‐mode feeding approach to the 2‐D square patch resonator is proposed and applied in the design of bandpass filter with wideband harmonic suppression. A second‐order bandpass filter centred at f0 = 4.0 GHz with wide stopband suppression has been implemented by using multilayer liquid crystal polymer (LCP) circuit technology.